Bürgergeld statt Hartz IV; Citizen's income ("Bürgergeld") or social welfare ("Hartz IV")? - Holger Schäfer (Wirtschaftsdienst, 2022)
– Germany's new government attempts once again to get rid of the infamous "Hartz IV" name for the country's basic income support. The new "Bürgergeld" not only sports a new name, it also formulates new rules for sanctions and for considering income and property.
Keywords: J65; J68; 330; Grundeinkommen; Deutschland